Application of the Whole Optimization of Emergency Nursing Model United and Its Influence on Patients’ Stress Response and Nursing Satisfaction - Dannan Ai; Sumin Xu (Applied Bionics and Biomechanics)
Objective. To investigate the use of an integrated emergency nursing model with a multidisciplinary team (MDT) teaching method for practice of nursing towards multiple trauma in the emergency department and its influence on patients’ stress response and nursing satisfaction. Methods. The research subjects were 120 multiple trauma patients hospitalized to our hospital’s emergency department between January 2019 and January 2020, who were evenly divided into groups A (n=60) and B (n=60) based on the sequence of admission. For patients in group A, on the basis of whole optimization of the emergency nursing model, the MDT teaching and training were given to the nursing staff in group A. Patients in group B had their emergency nursing model completely optimized. The assessment scores of nursing staff were compared. The patients’ C-reactive protein (CRP) levels in peripheral circulation, first-aid time indices, treatment effect, risk of complications & nursing contentment were all investigated. Results. Nursing personnel in group A had considerably higher achievement scores than staff nurses in group B (P<0.001). CRP levels in group A were considerably lower following therapy (P<0.05) than those in group B. The time it took for group A to receive first assistance was considerably less than that for group B (P<0.001). Group A had a considerably superior treatment effect than group B (P<0.05). Complications occurred at a lower rate in group A (P<0.05) than in group B. Group A nurses were more satisfied than group B nurses (P<0.05). Conclusion. The entire optimization of the emergency nursing model combined with the MDT way of teaching can abbreviate the rescue process, reduce stress, improve treatment effect & reduce the possibility of complications in multiple trauma patients in the emergency department, and patients seem to be more comfortable with this nursing model. As a result, it should become more well known.